Type V collagen-induced nasal tolerance prevents lung damage in an experimental model: new evidence of autoimmunity to collagen V in COPD - Robertoni, Fabíola Santos Zambon; Velosa, Ana Paula Pereira; Oliveira, Luana de Mendonça; Almeida, Francine Maria de; Silveira, Lizandre Keren Ramos da; Queiroz, Zelita Aparecida de Jesus; Lobo, Thays de Matos; Contini, Vitória Elias; Baldavira, Camila Machado; Carrasco, Solange; Fernezlian, Sandra de Morais; Sato, Maria Notomi; et al. (Frontiers in Immunology, 2024)
Chronic obstructive pulmonary disease (COPD) has been linked to immune responses to lung-associated self-antigens. Exposure to cigarette smoke (CS), the main cause of COPD, causes chronic lung inflammation, resulting in pulmonary matrix (ECM) damage. This tissue breakdown exposes collagen V (Col V), an antigen typically hidden from the immune system, which could trigger an autoimmune response. Col V autoimmunity has been linked to several lung diseases, and the induction of immune tolerance can mitigate some of these diseases. Evidence suggests that autoimmunity to Col V might also occur in COPD; thus, immunotolerance to Col V could be a novel therapeutic approach.